Domain Knowledge and Hindsight Bias among Poker Players. (5th September 2013) - Calvillo, Dustin P.; Rutchick, Abraham M.
ABSTRACT Hindsight bias occurs when individuals believe that events were more predictable after they have occurred than they actually were before they occurred. Although hindsight bias is a well‐studied phenomenon, few studies have examined the role of expertise in this bias. Two experiments investigated the relation between the magnitude of hindsight bias and self‐reported poker expertise (Experiment 1) and assessed poker knowledge (Experiment 2). In Experiment 1, self‐rated poker expertise was negatively correlated with hindsight bias. Experiment 2 employed memory and hypothetical hindsight conditions and found that poker knowledge was negatively correlated with hindsight bias in the memory condition, but unrelated to hindsight bias in the hypothetical condition. These results help elucidate the role of expertise in hindsight bias and provide additional support for the separate components view, which claims there are different forms of hindsight bias that are differentially affected by certain factors. Domain knowledge appears to be one of such factors. Copyright © 2013 John Wiley & Sons, Ltd.